National Association of Neonatal Nurse Practitioners (NANNP) Workforce Survey. (June 2015) - Kaminski, Mary M.; Meier, Susan; Staebler, Suzanne
Abstract : Background: As an integral member of a healthcare team, neonatal nurse practitioners (NNPs) provide care in a variety of settings that include but are not limited to all levels of inpatient care, transport, acute and chronic care settings; delivery rooms; and outpatient care settings. Anecdotal evidence indicates that responsibilities, practice environment, and workload vary widely between regions and practice settings. Purpose: Historically, the supply of neonatal nurse practitioners has rarely met the demand for services, although needs vary by region at any given time. Because the NNP role is a collaborative one, a shortage of NNPs leaves a gap in the team approach to care. In 2011, the National Association of Neonatal Nurse Practitioners (NANNP) commissioned the first national study of the current NNP workforce in the United States and Canada. In an effort to further explore the NNP workforce population, the NANNP Council partnered with the National Certification Corporation to perform a second workforce survey of NNPs in the spring of 2014. Findings/Results: The online survey was conducted between March and April 2014. The goal of the study was to describe the demographics, practice environment, scope of responsibilities, benefits and reimbursement, and job satisfaction for the current NNP workforce. Implications for Practice/Research: Key areas of concern identified by the 2014 Neonatal Nurse Practitioner Workforce Survey include an aging workforce; the need for NNP faculty; inadequate staffing ratios; the lack of downtime during prolonged shifts; and the need to assisting practices in developing competency and mentoring programs.